ICT and leadership styles-level of leadership competence of educational leaders - Yousef A. Baker, El-Ebiary; Mohd Hafiz, Yusoff@Che Abdullah; Seita, Almandeel (2020)
Researchers have studied the leadership styles of educational leaders in connection with their level of computer use and success in integration of ICT. This study aims to reveal if the leadership style can be a predictor of competent technology leaders. The importance of this study is to investigate the leaders’ competency as technology leaders rather than level of perceived use of technology, using Technology Leadership Competency Scale for Education Administrators which is adapted from International Society for Technology and Education (ISTE) standards for Education administrators. Fifty educators, who take leadership or administrative roles in educational institutions from the Eastern part of Malaysia as scope, completed Multi factor leadership questionnaire (MLQ) developed by Bass. The results indicate moderate correlation between both transactional and transformational leadership styles. It is concluded that leadership style is not a predictor of competency level of technology leadership. The study contributes into literature discussing the effects of cultural differences in different countries on desired leadership styles, which in result may affect the level of technology leadership competency. In addition, it also argues that leadership style characteristics cannot be used as a method to transform education.